2004
DOI: 10.1063/1.1846953
|View full text |Cite
|
Sign up to set email alerts
|

Formation of SiC-surface nanocrystals by ion implantation and electron beam rapid thermal annealing

Abstract: SiC-surface nanostructures on silicon were produced by 10keV carbon ion implantation into silicon followed by annealing to 1000°C for 15s under high-vacuum conditions using a raster-scanned electron beam. Following implantation, an amorphous layer is produced which starts at the surface and extends 65nm into the substrate. Following annealing, the implanted surface layer remains amorphous but becomes covered with semi-spherical crystalline features up to 300nm in diameter. The nanocrystals have been confirmed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 17 publications
(10 reference statements)
1
15
0
Order By: Relevance
“…3,4 Crystal growth occurs during electron-beam annealing under high vacuum conditions by diffusion of carbon and silicon atoms across the surface to nucleation sites randomly distributed across the entire surface. The circular cross-section of the nanocrystals suggests that such diffusion is isotropic, consistent with adatom diffusion on an amorphous surface.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Crystal growth occurs during electron-beam annealing under high vacuum conditions by diffusion of carbon and silicon atoms across the surface to nucleation sites randomly distributed across the entire surface. The circular cross-section of the nanocrystals suggests that such diffusion is isotropic, consistent with adatom diffusion on an amorphous surface.…”
Section: Discussionmentioning
confidence: 99%
“…Markwitz The calculated depth range of the implanted 13 C C ions corresponds well with cross-sectional transmission electron microscope measurements. 3 The samples were subsequently annealed with a highcurrent electron beam. During annealing under high vacuum conditions, a 20-keV electron beam with up to 2.5 mA current was raster-scanned over the targets to ensure homogeneous heating.…”
Section: Methodsmentioning
confidence: 99%
“…16 The nuclear reaction analysis (NRA) measurements using the 12 C(d,p) 13 C reaction at 920 keV 16 were used to search for carbon impurities after the implantation and annealing processes.…”
Section: Methodsmentioning
confidence: 99%
“…It is shown that the implanted carbon and nitrogen are retained at the surface, leading to the conclusion that the nanostructure incorporates Si, C, and N. This is consistent with our earlier studies of carbon-implanted silicon, on which crystalline SiC nanostructures were observed at the surface. 7 Electron emitters fabricated from SiCN would theoretically combine the properties of SiC and Si 3 N 4 , namely high thermal conductivity, high strength, and excellent corrosion and wear resistance. 8 Previous reports of SiCN field emitters, including thin-film structures 9,10 and nanostructures, 11,12 have confirmed excellent potential for field-emission applications.…”
Section: Introductionmentioning
confidence: 99%